Stages d'enseignement dans les commissions scolaires anglophones du Québec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Chaque année, le gouvernement provincial finance des expériences de formation supervisées en milieu scolaire pour les stagiaires en enseignement, appelées « stages d’enseignement ». Le présent résumé examine la répartition de ces fonds entre les neuf commissions scolaires anglophones en fonction de la proportion de stagiaires en enseignement qu’elles accueillent en provenance des universités québécoises. Les données mettent en évidence une concentration des stages d’enseignement dans les commissions scolaires situées à proximité des universités anglophones et dans le grand Montréal, ce qui désavantage certaines écoles en régions rurales et éloignées.

Student Teacher Practicums in English School Boards in Quebec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Each academic year the provincial government provides financial support for supervised, in-school training experiences for student teachers, known as teaching practicums. This brief examines how these funds are distributed across the nine English school boards based on the proportion of student teachers they host from Quebec universities. The data highlights a concentration of teaching practicums undertaken in school boards with proximity to English universities and Greater Montreal, thereby disadvantaging some rural and remote schools.

EPCA Quebec Applauds Quebec Government's $300-Million Academic Catch-Up Plan: A Boost for Student Success - English Parents' Committee Association (EPCA) (2024)

Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

Grâce à un financement de 1,1 million de dollars, 10 projets novateurs du FIC 2.0 prêtent assistance à 1 500 jeunes et aînés du Québec d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Powered with $1.1 Million of Funding, 10 Innovative CIF 2.0 Projects Benefit 1,500 Youth and Seniors Across English-speaking Quebec - Quebec Community Groups Network (QCGN) (2023)

Renforcer la vitalité des communautés d'expression anglaise du Québec : Cadre normatif 2022-2025 - Québec. Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA) (2023)

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Legault Government Must Backtrack on Dawson Decision: QCGN - Quebec Community Groups Network (QCGN) (2022)

QCGN : le gouvernement Legault doit faire marche arrière concernant sa décision au sujet de Dawson - Quebec Community Groups Network (QCGN) (2022)

ArtistsInspire Grants COVID-19 Protocol - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Funding Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Projet 294 : Perspectives from Parents on the Overhaul of the Funding and Organization of Services for Handicapped Students and Students With Social Maladjustments or Learning Difficulties - English Parents' Committee Association (EPCA) (2021)

EPCA Lauds New Monies, Lifitng of Bureaucratic Controls : Disappointed in Lack of Option for Parents - English Parents' Committee Association (EPCA) (2020)

[Update to Parents Regarding Government Initiatives for 2020 School Year] - English Parents' Committee Association (EPCA) (2020)

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)